تجربة استخدام طلبة جامعة الوادي للبوابة الإلكترونية لقسم العلوم الإنسانية والإجتماعية وأثره في تعزير التعليم عن بعد - زياد, اسماعيل (جامعة الوادي - University of Eloued, 2023)
تستهدف الدراسة التعرف على تجربة استخدام طلبة جامعة الوادي للبوابة الإلكترونية لقسم العلوم الإنسانية والإجتماعية، وأثرها في تعزيز على التعليم عن بعد. اعتمدت الدراسة على المنهج المسحي، واستمارة الاستبيان كأداة لجمع البيانات، أسلوب العينة القصدية، وتوصلت الدراسة فيما بعد إلى مجموعة من النتائج. Abstract: The study aims to identify the experience of eloued University students using the electronic portal of the Department of Humanities and Social Sciences, and its impact on promoting distance education. The study relied on the survey method, the questionnaire as a tool for data collection, the intentional sampling method, and the study later reached a set of results.
دراسة ميدانية
مقال
Keywords: تجربة استخدام ; طلبة جامعة الوادي ; البوابة الإلكترونية ; التعليم عن بعد ; دراسة ميدانية; Experience, use, students of el oued University, the electronic portal of the Department of Humanities and Social Sciences, impact, Promoting distance education, a field study